Genomic diversity and functional adaptation of Limosilactobacillus reuteri isolated from diverse ecological niches - Sun, Yuexin; Zhao, Qian; Li, Weicheng; Kwok, Lai-Yu; Zhang, Heping (Frontiers in Microbiology, 2025)
Limosilactobacillus reuteri is a widely utilized probiotic, however, the genomic diversity and evolutionary mechanisms underlying its adaptation to various hosts and environments remain incompletely understood. This study employed comparative genomics to analyze 176 L. reuteri genomes from animal (rodents, mammals, ruminants, and birds), human intestinal, and food sources (dairy products, fermented foods; 89 newly sequenced and 92 retrieved, 5 excluded by ANI < 95%). We assessed genomic features, average nucleotide identity, pan/core genomes, carbohydrate-active enzymes, bacteriocin production, CRISPR-Cas systems, and antibiotic resistance genes. The pan-genome consisted of 16,814 genes, while the core genome contained 553 genes. Core-gene phylogeny revealed seven clades, rodents isolates were positioned closer to the root. The clustering trend of fermented foods isolates in the phylogenetic tree may indicate that these strains have undergone convergent evolution or adaptive evolution in a specific environment. CAZymes varied across sources, and the predicted bacteriocin clusters were enriched in animal-derived, particularly in rodent isolates. CAZy functional composition in L. reuteri is shaped by the ecological niche and host environment, reflecting a pattern of host-driven evolutionary adaptation. CRISPR–Cas systems were present in 23.3% of genomes, predominantly in rodents isolates, indicating strong anti-phage capabilities. The heterogeneity of CRISPR-Cas systems among sources suggests that subpopulations of L. reuteri have been subjected to different evolutionary pressures. The predominance of Type II systems agrees with their widespread occurrence in lactobacilli. The presence of multiple probiotic function-related genes across all separation sources confirms the robust probiotic potential of L. reuteri. Antibiotic resistance genes, including tet, ermB, and vatE, were most prevalent among animal-derived isolates, with the highest numbers occurring in mammals and the lowest in rodents. Therefore, strain-specific safety assessments are necessary prior to clinical or food applications. The findings underscore the significance of host-specific adaptations in shaping the genetic and functional profiles of L. reuteri, offering valuable implications for its application in food-derived, human-derived, animal-derived and therapeutics.